2008
DOI: 10.1063/1.2952290
|View full text |Cite
|
Sign up to set email alerts
|

A transparent cell-culture microchamber with a variably controlled concentration gradient generator and flow field rectifier

Abstract: Real-time observation of cell growth provides essential information for studies such as cell migration and chemotaxis. A conventional cell incubation device is usually too clumsy for these applications. Here we report a transparent microfluidic device that has an integrated heater and a concentration gradient generator. A piece of indium tin oxide ͑ITO͒ coated glass was ablated by our newly developed visible laser-induced backside wet etching ͑LIBWE͒ so that transparent heater strips were prepared on the glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…At low flow rate of 20µL/hr, due to the low molecular weight (6045 Da) and the electrophoresis of EGF, a slight concentration difference occurred near the zigzag channel. In our previous work, we have found that the diffusion simulation is in accordance with the experimental data [48]. Therefore, cells were observed in the regions with uniform chemical concentration and EF (Figure 1).…”
Section: Methodssupporting
confidence: 85%
“…At low flow rate of 20µL/hr, due to the low molecular weight (6045 Da) and the electrophoresis of EGF, a slight concentration difference occurred near the zigzag channel. In our previous work, we have found that the diffusion simulation is in accordance with the experimental data [48]. Therefore, cells were observed in the regions with uniform chemical concentration and EF (Figure 1).…”
Section: Methodssupporting
confidence: 85%
“…For example, Lin et al (2007) successfully developed an ITO based microheater chip for in situ fluid heating and thermal control in a microchip for cell immobilization application. More recently, Cheng et al (2008) proposed a similar chip with uniform temperature distribution and long-term thermal stability for cell culture purpose. The fabrication procedures of those ITO-based heating device involved the use of traditional wet etching approach and of laser-induced backside wet etching respectively to pattern ITO on a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Both the development of CO 2 laser treatment of polymethylmethacrylate (PMMA) (Refs. 18 and 19) and the application of these modified plastics 20,21 have been reported. A recent example of the use of laser ablation for microchannel development based on a 3 layer PMMA laminate utilized two different types of lasers.…”
Section: Introductionmentioning
confidence: 99%